Are Genes Us? - Cranor, Carl F. (Book collections on Project MUSE., 1994)
Do our genes make us human? More than a billion dollars are being spent on the Human Genome Project to map the genes on human DNA. Along with the hope of controlling many terrible diseases, the project offers the threat of changing the behavior and the qualities that define us as human. The contributors to this volume argue that, to predict the social, political, and ethical consequences of the new genetics, we dare not take even the science for granted. Coming from fields as diverse as biology, law, sociology, history of science, gender studies, political science, philosophy, and rhetoric, the contributors take a hard look at the presuppositions, concepts, language and self-descriptions of genetics itself. How has the focus on genes affected medical research and our conceptions of humanity? How have scientists closed off areas of the Human Genome Project from serious ethical discussion? How do such metaphors as code of life and master gene subtly influence our thinking? How can genes cause disease? How might well-intentioned genetic technologies harm society at large? And how did we go ahead with the new genetics without asking these questions first? These clear-headed essays go beyond stock criticisms of the new genetics; a comprehensive bibliography covers the ethical, legal, and social implications of the Human Genome Project. This is essential reading for everyone concerned about the Human Genome Project, biotechnology, science, medicine, bioethics, and society.